Self-reported treatment, workplace-oriented rehabilitation, change of occupation and subsequent sickness absence and disability pension among employees long-term sick-listed for psychiatric disorders: a prospective cohort study - Bryngelson, Anna (BMJ Group, 2012)
AIM: To examine whether self-reported treatments, workplace-oriented rehabilitation and change of occupation were associated with subsequent sickness absence and disability pension among long-term sick-listed for psychiatric disorders. DESIGN: A prospective cohort study. SETTING AND PARTICIPANTS: 5200 employees (80% from the Swedish municipalities and county councils and 20% manual workers from the Swedish industry) were randomly selected who in 1999 in the register of AFA Insurance had a new spell of long-term sickness absence due to a psychiatric disorder. Of these, 99 were excluded (duplicates and deaths, persons living abroad, with protected personal information), and 5101 received a questionnaire in 2001. 3053 individuals responded (60%). After the exclusion of employees with no sick leave in 1999 according to the Swedish social insurance agency, aged 62 years and older, with disability pension 1999–2001, no self-reported treatment, and with missing information on the covariates, our final study group was 2324 individuals. Logistic regression analyses were performed. OUTCOME MEASURES: Sickness absence (>90 days) and disability pension (>0 day). RESULTS: 45% had sickness absence and 18% a new disability pension in 2002. Drug treatment and physiotherapy, respectively, were associated with increased odds of sickness absence (OR 1.56, 95% CI 1.28 to 1.90; OR 1.43, 95% CI 1.21 to 1.69), and disability pension (OR 1.79, 95% CI 1.34 to 2.41; OR 1.75, 95% CI 1.40 to 2.18). Workplace-oriented rehabilitation and change of occupation, respectively, reduced the odds of sickness absence (OR 0.70, 95% CI 0.59 to 0.83; OR 0.35, 95% CI 0.27 to 0.45). CONCLUSIONS: We found a pattern of poorer outcome of drug treatment and physiotherapy compared with other treatments (psychotherapy, workplace-oriented rehabilitation and complementary or alternative medicine) in terms of increased odds of sickness absence and disability pension. Workplace-oriented rehabilitation and/or change of occupation were associated with reduced odds of sick leave. Studies with a randomised controlled trial design are needed to examine the effect on sick leave of a workplace-oriented intervention.